2017
DOI: 10.5144/0256-4947.2017.455
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of pediatric status epilepticus in 116 Saudi patients: predictors of outcome

Abstract: BACKGROUNDStatus epilepticus (SE) is a common, life-threatening condition. Multiple factors are used to predict its outcome and evaluate its risks, and there have been only a few studies in Saudi Arabia.OBJECTIVESInvestigate predictors of SE outcome.DESIGNRetrospective chart review study.SETTINGTertiary center, Riyadh.PATIENTS AND METHODSWe reviewed all pediatric cases (age 14 years or younger) of SE admitted between January 2005 and December 2015, collecting data on age, sex, date of birth, developmental stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…have been listed as predictors of poor outcome. 6,[15][16][17][18][19] In the present study, female gender, SE duration > 1 hour before presentation, generalized onset seizures, need for critical care support, poor response to initial antiepileptic therapy, and acute symptomatic etiology were found as predictors of poor outcome.…”
Section: Discussionsupporting
confidence: 46%
“…have been listed as predictors of poor outcome. 6,[15][16][17][18][19] In the present study, female gender, SE duration > 1 hour before presentation, generalized onset seizures, need for critical care support, poor response to initial antiepileptic therapy, and acute symptomatic etiology were found as predictors of poor outcome.…”
Section: Discussionsupporting
confidence: 46%
“…28,29 This result differs from the previous Saudi study in KAMC, which showed no difference between males and females. 11 Further, SE incidence was more prominent among children of non-Saudi origin than those of Saudi origin. Ethnic origin as a causative factor of epilepsy was also found in an American study, which demonstrated that the non-Hispanic black population's mortality rate was higher than that of the Hispanic population.…”
mentioning
confidence: 94%
“…This difference is attributed to the fact that referral centers usually have a low number of febrile SE as KAMC. 11 In a Japanese study, children below the age of 15 )49.3%( were found to be affected by SE due to febrile seizure; 7 on the other hand, other European research studies have shown that the occurrence of SE can be attributed to cerebrovascular pathology )34-60%(. 18,19 In another study, 17% of the total included SE cases were caused either due to metabolic disorder or CNS infection.…”
mentioning
confidence: 96%
“…Several studies have shown that patients with short SE durations have better outcomes [ [36] , [37] , [38] , [39] ] owing to fewer SE-related complications, such as tachycardia, hypoglycemia, hypotension, or rhabdomyolysis, although a few studies yielded inconclusive results [ 40 ]. Patients with acute symptomatic SE have a three-fold greater risk of developing chronic epilepsy compared to patients with acute symptomatic seizures [ 1 ].…”
Section: Discussionmentioning
confidence: 99%